Pelaksanaan Praktek Kerja Lapangan Kelas Xi Jurusan Teknik Instalasi Tenaga Listrik di SMKN 2 Kota Serang di Masa Pandemi Covid-19 - Mochamad Asep Soedarma; Irwanto Irwanto; Endi Permata (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study is to describe: 1) PKL planning. 2) implementation of street vendors. 3) monitoring and evaluation. 4) Testing and Certification. and 5) The results of street vendors at SMKN 2 Serang City, Serang, Banten. This research is a qualitative descriptive study. The subjects of this research are the PKL Coordinator, Public Relations WK, Curriculum WK, Teacher Advisors, Students, and Industrial Advisors. Data collection techniques with interviews, documentation studies, and observation. Test the validity of the data using triangulation of sources and methods. Data analysis used a qualitative analysis of the Miles & Huberman interactive model, namely data reduction, data presentation, and drawing conclusions. The results of the study show the following: 1) PKL preparation starts from the legal basis, PKL Team, Correctional, PKL Understanding, Cooperation between Vocational Schools and IDUKA, Work Programs, Curriculum Synchronization, Human Resources, Financing, 2) Implementation of PKL at SMKN 2 Serang City is in semester 3 grade 2, with a minimum of 1 month and a maximum of 3 months. The implementation of street vendors at SMKN 2 Serang City has several activities, namely debriefing, student selection, compiling syllabus and activity schedules, IDUKA contracts, learning, and guidance. 3) Monitoring and Evaluation, Implementation Team, Time, Components to be monitored, Instruments, Utilization of monitoring results. 4) Testing and Certification, at SMKN 2 Serang city there is no testing, only the making of a report on the completion of street vendors and the certification here is only limited to the information that the person concerned has finished street vendors. 5) The results of street vendors, the competencies obtained by participants vary and the suitability of the curriculum, some say it is quite appropriate. Keywords: Implementation; Field Work Practice; Vocational School